The Scream of Dissent: Exploring Ginsberg’s Sub(Verse)Ive ‘Howl’ in the Post-War America - Ramteke, Vishant (Journal of Advanced Research in English & Education, 2022)
Inspired by its predecessor, Transcendentalism, a new generation of poets came to the fore in the literary canon, challenging the mainstream cultural and political landscape in America. The quintessential soul of ‘dissent’ came to embody the Beat generation. At the centre of it are the three people and their entire being consolidated its core values, along with their path breaking texts; On the Road by Jack Kerouac, The Naked Lunch by William Burroughs, and Howl by Allen Ginsberg. The paper seeks to establish the essence of the Beat generation through an analysis of Howl that disseminated ideals which were, and are still, considered to be subversive; experimentation with mind altering drugs, sexual liberation, rejection of materialism. The expansion of such unconventional ideals were not limited to the cultural mores but also ruptured the rigid structure of literature. How to cite this article:  Ramteke VA. The Scream of Dissent: Exploring Ginsberg’s Sub(Verse)Ive ‘Howl’ in the Post-War America. J Adv Res Eng & Edu 2022; 7(1): 14-18. DOI: https://doi.org/10.24321/2456.4370.202215